Age determination of Mosaik L1 (MOS_L1) peat core from Canada - Simon van Bellen (PANGAEA, 2021)
14C and 210Pb age determination of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Projec